An Autopsy Case of Fulminant Hepatitis in a Patient with Multiple Sclerosis Treated by Interferon-Beta-1a - Yamazaki, Yuichi (Intern Med, 2017)
A 44-year-old woman with multiple sclerosis (MS) receiving interferon (IFN)-beta-1a treatment was admitted to a local hospital for severe icterus and liver injury. She was transferred to our university hospital because fulminant hepatitis (FH) was suspected. She was diagnosed with acute-type FH based on hepatic coma, severe liver injury and liver failure, and she received plasma exchange and continuous hemodiafiltration therapy. On hospital day 6, she died from liver failure despite intensive care. An autopsy revealed histological findings consistent with FH. Physicians should monitor the hepatic function of MS patients receiving IFN-beta-1a treatment, as serious events can occur in rare cases.